2020
DOI: 10.1080/14756366.2019.1705292
|View full text |Cite
|
Sign up to set email alerts
|

Biological exploration of a novel 1,2,4-triazole-indole hybrid molecule as antifungal agent

Abstract: (2-(2,4-Dichlorophenyl)-3-(1H-indol-1-yl)-1-(1,2,4-1H-triazol-1-yl)propan-2-ol (8 g), a new 1,2,4-triazole-indole hybrid molecule, showed a broad-spectrum activity against Candida, particularly against low fluconazolesusceptible species. Its activity was higher than fluconazole and similar to voriconazole on C. glabrata (MIC 90 ¼ 0.25, 64 and 1 mg/mL, respectively), C. krusei (MIC 90 ¼ 0.125, 64 and 0.125 mg/mL, respectively) and C. albicans (MIC 90 ¼ 0.5, 8 and 0.25 mg/mL, respectively). The action mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…CYP3A4, CYP2D6). Recently, we published extended biological exploration of 8g (in vitro and in vivo assays) and then we confirmed the full potential of this molecule [28]. Another major challenge is the emergence of resistance to azole antifungals among Candida species [58].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…CYP3A4, CYP2D6). Recently, we published extended biological exploration of 8g (in vitro and in vivo assays) and then we confirmed the full potential of this molecule [28]. Another major challenge is the emergence of resistance to azole antifungals among Candida species [58].…”
Section: Discussionmentioning
confidence: 55%
“…Comparison of this sub-series with the 1,2,4-triazole sub-series (unsubstituted indole derivatives 11a, 11b, and 11d) has shown that the triazole moiety decreased significantly the cytotoxicity (IC 50 > 100 µM), except for the 4-bromo derivative 11c (IC 50 = 38 µM), 8g, and its enantiomers. Indeed, the cytotoxicity values of 8g, (+)-(R)-8g, and (−)-(S)-8g (IC 50 = 35 µM [28], 32, and 30 µM, respectively) were two times higher than that of KTC and at least three times higher than those of FLC (IC 50 > 100 µM).…”
Section: Toxicity Of Selected Compounds On Human Fetal Lung Fibroblasmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, compound 1d could offer a new treatment strategy known as combo-therapy in the use of new azole antifungals recently designed. 47,48 Nevertheless further chemical modications will be carried out to synthetize a second generation of piperazinyl-pyrrolo[1,2-a]quinoxaline derivatives designed specically as EPIs of the pathogenic yeast C. albicans. Once again, compound 1d will be investigated for assessing the structural importance of its benzhydryl moiety (e.g.…”
Section: Discussionmentioning
confidence: 99%